First heterozygous NOP10 mutation in familial pulmonary fibrosis. Issue 6 (11th June 2020) - Kannengiesser, Caroline; Manali, Effrosyni D.; Revy, Patrick; Callebaut, Isabelle; Ba, Ibrahima; Borgel, Adrien; Oudin, Claire; Haritou, Aggeliki; Kolilekas, Lykourgos; Malagari, Katerina; Borie, Raphael; Lainey, Elodie; et al.
Germline telomere-related gene mutations are associated with familial pulmonary fibrosis and lead to short telomere syndrome [1, 2] . Most of the short telomere syndrome-related genes, such as TERT, TERC, DKC1, TINF2, NHP2 and NOP10, were identified in dyskeratosis congenita patients with early onset mucocutaneous manifestations and/or bone marrow failure [3]. The telomerase complex includes TERT, the TERC RNA and DKC1. NOP10, along with DKC1, NHP2 and GAR1, is essential for TERC stability and telomere maintenance [4]. Homozygous NOP10 mutation (c.100C>T, p.Arg34Trp) has been reported only once in a consanguineous family with autosomic recessive dyskeratosis congenita without pulmonary fibrosis [5]. Moreover, the p.Arg34Trp NOP10 mutation caused telomere shortening in homozygous and heterozygous carriers [5]. Here we provide evidence that a heterozygous NOP10 mutation (c.17A>G, p.Tyr6Cys) identified in a large family co-segregates with adult-onset familial pulmonary fibrosis. We provide first evidence that a heterozygous NOP10 mutation (c.17A>G, p.Tyr6Cys) identified in a large family co-segregates with adult-onset familial PF and predisposes to short telomere syndrome (familial PF, liver, haematological diseases) http://bit.ly/2wvXsUd